Poly(aspartic acid)–tryptophan grafted copolymer and its scale‐inhibition performance. Issue 45 (12th August 2015) - Sun, Xiaoyu; Zhang, Junping; Yin, Chengxian; Zhang, Juantao; Han, Jiao
ABSTRACT Scale deposition, which severely damages oil exploration, is a difficulty encountered in oil fields. Scale inhibitors are widely used for controlling scales. Poly(aspartic acid) (PASP) is attracting more and more attention with increasing environmental concern and discharge limitations. However, PASP's poor inhibition in a high‐temperature environment markedly limits its wide use. Thus, poly(aspartic acid)–tryptophan grafted copolymer (PASPTR) was synthesized to improve the inhibition efficiency of PASP. The results show that the reactant of PASPTR has a great effect on its inhibition performance. PASPTR was found to inhibit the precipitation of CaSO4 close to 90% at concentrations as low as 0.4 mg/L at 50°C. The inhibition efficiency of PASPTR against CaCO3 was close to 100% with the concentration of 2 mg/L at 50°C. Scanning electron microscopy and X‐ray diffraction analyses, which showed the morphological and crystal structural changes of CaCO3 and CaSO4 precipitation, verified the excellent inhibition performance of PASPTR. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42739.